2017
DOI: 10.1021/acscatal.6b03706
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Electroreduction on Au/TiC: Enhanced Activity Due to Metal–Support Interaction

Abstract: CO2 electroreduction technology is considered an important example of efficient carbon-containing energy sources. Herein, we introduce the metal–support interaction effect with a TiC support for Au/TiC electrocatalysis, which exhibits considerably enhanced activity and selectivity for electroreduction of CO2 to CO while suppressing H2 evolution. With this catalyst, an important electronic effect for CO2 electroreduction was clearly elucidated. Local sp-band charge transfer and d-band shifts play an important r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 39 publications
0
49
0
Order By: Relevance
“…Changes in the electronic and geometric structure via altering the shape of nanoparticles, forming alloys, or nanocomposites have proved to be useful tools for the selectivity of CO 2 reduction on metallic catalysts. The presence of different atoms or molecules and the changes in the interatom spacing can lead to the strain and ligand effect to the electronic and geometric structures of catalysts, by affecting their capability of binding to the adsorbed intermediates .…”
Section: Design Of Electrocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the electronic and geometric structure via altering the shape of nanoparticles, forming alloys, or nanocomposites have proved to be useful tools for the selectivity of CO 2 reduction on metallic catalysts. The presence of different atoms or molecules and the changes in the interatom spacing can lead to the strain and ligand effect to the electronic and geometric structures of catalysts, by affecting their capability of binding to the adsorbed intermediates .…”
Section: Design Of Electrocatalystsmentioning
confidence: 99%
“…In the case of In (1− x ) Ni x alloys, the highest CO FE of 60% was observed at the same potential when x = 0.02. Recently, Kim and co‐workers studied the CO 2 electroreduction on Au/TiC catalysts with an enhanced activity resulting from the electronic structure effect brought by the metal–support interaction . The metal–support interaction greatly affects the electronic structure change in Au metals.…”
Section: Design Of Electrocatalystsmentioning
confidence: 99%
“…[2,3] Moreover,CO 2 RR in aqueous solution inevitablyc ompetes with the hydrogene volution reaction( HER), resultingi nad ifficult separation of the complex products. [6][7][8] Compared with the above-mentioned metals,c arbon materials have drawn significant attention owing to their low cost and high selectivity for CO 2 RR. Additionally, other groups of metal catalysts have shown medium overpotentialf or HER and suitable CO adsorption (e.g.,Z n, Cu, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…[13] However,t he limited reserves and high price of the precious metals are ab arrier for large-scale applications. [25][26][27][28] Them ost commonly studied TMCs (for example,M o 2 Ca nd WC) are excellent supports for HER, leading to ar eduction of the selectivity of the CO 2 RR products. [21][22][23][24] Currently, only af ew theoretical studies on the CO 2 RR over metalmodified TMCs were reported while few experimental studies were reported.…”
mentioning
confidence: 99%
“…[21][22][23][24] Currently, only af ew theoretical studies on the CO 2 RR over metalmodified TMCs were reported while few experimental studies were reported. [25][26][27][28] Them ost commonly studied TMCs (for example,M o 2 Ca nd WC) are excellent supports for HER, leading to ar eduction of the selectivity of the CO 2 RR products. [29,30] Therefore,e xploring other TMCs as potential supports for CO 2 RR is necessary.H erein, Pd catalysts on different TMCs are studied for CO 2 RR using thin films, powder catalysts,i nsitu characterizations,a nd DFT calculations.E xperimental results demonstrate that the TMC substrates modify the CO 2 RR performance.Pdsupported on TaC exhibits higher activity than Pd on other TMC substrates (Mo 2 C, WC,N bC) and the commercial Pd/C catalysts.T he ratios of the syngas products (H 2 /CO) are close to those desired for methanol and Fischer-Tropsch synthesis.M eanwhile,t he Pd loading of Pd/TaC has been significantly reduced compared with commercial Pd/C.I nsitu X-ray absorption spectroscopy (XANES and EXAFS) and in situ X-ray diffraction (XRD) demonstrate that the supported Pd is transformed to PdH during CO 2 RR, while TMC substrates exhibit no phase change.D FT calculations reveal that the TMC substrates affect the CO 2 RR performance via adjusting the energetics for *HOCO formation, the key step for CO 2 RR, thus facilitating the reaction kinetics and enhancing the CO 2 RR performance.T hese results suggest that TaCi s ap romising low-cost candidate for reducing the usage of precious metals and increasing the catalyst performance for CO 2 RR.…”
mentioning
confidence: 99%